Cellular senescence in normal mammary gland and breast cancer: implications for cancer therapy - Sirinian, Chaido; Peroukidis, Stavros; Kriegsmann, Katharina; Chaniotis, Dimitrios; Koutras, Angelos; Kriegsmann, Mark; Papanastasiou, Anastasios D. (Genes, 2022)
Cellular senescence (CS) is a major homeostatic biological process, which plays a key role in normal tissue development and provides protection from stressful cell insults. The role of CS in mammary-gland development and breast cancer is not well understood. While there is a lack of experimental data on the role of CS in the development of the pre-pubertal mammary gland, there is evidence for a biphasic senescence response in adult normal-mammary-epithelial cells, where the bypass of the first senescence barrier (M0) seems to be a key step in the development of premalignant lesions, with genetic abnormalities that resemble in situ breast carcinoma. Further, there is accumulating evidence for the role of cellular senescence in breast-cancer response, regarding treatment and patient outcome. Here, we review the current literature on cellular senescence, in epithelial-mammary cells, breast-cancer cells, and breast-tumor-microenvironment-resident cells. Furthermore, we discuss its putative role in breast-cancer response, regarding treatment and disease progression. In addition, we provide preliminary evidence of CS in breast-cancer-microenvironment cells, such as tumor-associated fibroblasts and tumor-infiltrating lymphocytes, by employing the novel GL13 lipofuscin stain, as a marker of cellular senescence.